Nuclear receptor DHR96 acts as a sentinel for low cholesterol concentrations in Drosophila melanogaster. - Bujold, M.; Gopalakrishnan, A.; Nally, E.; King-Jones, K. (Molecular and Cellular Biology, 2010)
All eukaryotic cells have to maintain cholesterol concentrations within defined margins in order to function normally. Perturbing cholesterol homeostasis can result in a wide range of cellular and systemic defects, including cardiovascular diseases, as well as Niemann-Pick and Tangier diseases. Here, we show that DHR96 is indispensable for mediating the transcriptional response to dietary cholesterol and that it acts as a key regulator of the Niemann-Pick type C gene family, as well as of other genes involved in cholesterol uptake, metabolism, and transport. DHR96 mutants are viable and phenotypically normal on a standard medium but fail to survive on diets that are low in cholesterol. DHR96 mutants have aberrant cholesterol levels, demonstrating a defect in maintaining cholesterol homeostasis. Remarkably, we found that a high-cholesterol diet phenocopied the genomic profile of the DHR96 mutation, indicating that DHR96 resides at the top of a genetic hierarchy controlling cholesterol homeostasis in insects. We propose a model whereby DHR96 is activated when cellular cholesterol concentrations drop below a critical threshold in order to protect cells from severe cholesterol deprivation.